APPRENTICESHIP SKILLS DEVELOPMENT WITHIN THE INFORMAL SECTOR OF THE GHANAIAN ECONOMY: THE CASE OF SUNYANI MAGAZINE - Korang, V. (UDS International Journal of Development, 2021)
Apprenticeship training is one of the several means of developing the skills and competencies of the workforce in every economy. The small and micro-scale engineering enterprises since their inception, have been contributing towards the development of the country. This is particularly so in the manufacturing and engineering sectors where local tools, equipment and machinery are produced and serviced. The Sunyani magazine has become an emerging informal industrial zone where technical skills development is offered to individuals across different areas of engineering. This paper examined the nature of apprenticeship skills development and the associated challenges in an informal industrial zone through a cross-sectional survey. The findings suggest that on-the-job training model without pre- or post-training exams or test characterised the training of apprentices. During the skills development process of the apprentices, the master craftsmen examine the progress of the apprentices to ensure they are progressing and to determine when apprentices have acquired the needed skills to be considered certified. Despite the benefits offered to the local economy, lack of funding for new ventures, lack of government support, tools and equipment constrain the capacity of the informal industrial zone to scale-up its training capacity with the potential of being of greater benefits to the socioeconomic development of the country.